#TITLE_ALTERNATIVE# - NUR (NIM 12206063); Pembimbing: Ir. Tutuka Ariadji, M.Sc., Ph.D., ILHAMI
This analysis study attempts to design an ESP for simultaneously producing water and oil wells with the presence of gas based on field data. The parameters studied are pump setting depth, GOR, water cut and pump HP. The studied parameters shows that the pump setting depth has a great influence on the percentage of gas entering the pump, thus increases the fluid volume inside. The increased fluid volume due to gas can reach up to 350% with certain parameters when it is compared with the absence of gas. Also considering the pump HP, the presence of gas can increase the required HP of the pump up to 5-25% compared with the required pump HP without the presence gas. This study also provides a new nomograph to determine the volume of fluid and the percentage of gas entering the pump so that the calculation becomes much easier and simple. After the validation test, the nomograph has a maximum relative error of about 15%.